Opposite Predictive Value of Pulse Pressure and Aortic Pulse Wave Velocity on Heart Failure With Reduced Left Ventricular Ejection Fraction: Insights From an Eplerenone Post–Acute Myocardial Infarction Heart Failure Efficacy and Survival Study (EPHESUS) Substudy - Regnault, Veronique; Lagrange, Jérémy; Pizard, Anne; Safar, Michel E.; Fay, Renaud; Pitt, Bertram; Challande, Pascal; Rossignol, Patrick; Zannad, Faiez; Lacolley, Patrick (Hypertension (Dallas, Tex. 1979), 2014)
Although hypertension contributes significantly to worsen cardiovascular risk, blood pressure increment in subjects with heart failure is paradoxically associated with lower risk. The objective was to determine whether pulse pressure and pulse wave velocity (PWV) remain prognostic markers, independent of treatment in heart failure with reduced left ventricular function. The investigation involved 6632 patients of the Eplerenone Post–Acute Myocardial Infarction Heart Failure Efficacy and Survival Study. All subjects had acute myocardial infarction with left ventricular ejection fraction <40% and signs/symptoms of heart failure. Carotid-femoral PWV was measured in a subpopulation of 306 subjects. In the overall population, baseline mean arterial pressure <90 mm Hg was associated with higher all-cause death (hazard ratio, 1.14 [95% confidence interval, 1.00–1.30]; P<0.05), whereas higher left ventricular ejection fraction or pulse pressure was associated with lower rates of all-cause death, cardiovascular death/hospitalization, and cardiovascular death. In the subpopulation, increased baseline PWV was associated with worse outcomes (all-cause death1.16 [1.03–1.30]; P<0.05 and cardiovascular deaths1.16 [1.03–1.31]; P<0.05), independent of age and left ventricular ejection fraction. Using multiple regression analysis, systolic blood pressure and age were the main independent factors positively associated with pulse pressure or PWV, both in the entire population or in the PWV substudy. In heart failure and low ejection fraction, our results suggest that pulse pressure, being negatively associated with outcome, is more dependent on left ventricular function and thereby no longer a marker of aortic elasticity. In contrast, increased aortic stiffness, assessed by PWV, contributes significantly to cardiovascular death.